Multi-faceted outlook on the genre of corporate annual reports / Misyana Susanti Husin, Afida Mohd Ali and Shameem Rafik Galea - Husin, Misyana Susanti; Mohd Ali, Afida; Rafik Galea, Shameem (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
This article reviews recent studies (post 2000) on the genre of corporate annual reports (CARs). Subsumed under the umbrella of corporate disclosure discourse, this genre has been scrutinised from multi-disciplinary angles, ranging from accounting, linguistics to business communication. This paper presents various theoretical perspectives which have been applied to this genre, including legitimacy theory, genre theory, semiotics, communication and business management theories. The variables which are mainly studied in annual reports pertain to readability, form and communicative functions, moves, structure, concealment of negatives and Pollyanna effect, corporate social responsibility, gender roles, corporate culture of companies, promotional strategies and mythmaking. This review also provides insight into the methods used in analysing CARs from content analysis to corpus linguistics. Narrowing down the literature towards language analysis, the review revealed a gap in methodology in combining textual analysis with semiotics in relation to the practice of corporate social responsibility (CSR) or sustainability practices, especially in Malaysia. This is probably due to the fact that CSR reporting is still at its infancy stage and including it in the annual reports is still on a voluntary basis by the companies.